2004
DOI: 10.2165/00003088-200443120-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Budesonide (Entocort??? EC) Capsules for Crohn???s Disease

Abstract: This overview summarises available pharmacokinetic data on budesonide capsules (Entocort EC), approved for the treatment of mild-to-moderate active Crohn's disease involving the ileum and/or ascending colon and for prolongation of symptom control. Budesonide is a locally-acting glucocorticosteroid with an extensive, primarily hepatic, metabolism after oral administration. It is rapidly absorbed and biotransformed by cytochrome P450 (CYP) 3A to metabolites with negligible glucocorticoid activity. Entocort EC, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 70 publications
2
129
1
2
Order By: Relevance
“…The systemic availability of budesonide from MMX®-tablets matches that of marketed formulations [3]. However, the time to reach maximum plasma concentrations for the MMX®-tablets was prolonged from 6 h [10] to 14 h, which might be a measure of the projected slow and graded budesonide release throughout the colon.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The systemic availability of budesonide from MMX®-tablets matches that of marketed formulations [3]. However, the time to reach maximum plasma concentrations for the MMX®-tablets was prolonged from 6 h [10] to 14 h, which might be a measure of the projected slow and graded budesonide release throughout the colon.…”
Section: Discussionmentioning
confidence: 98%
“…This time-and pH-dependent delivery system consists of enteric coated (Eudragit L) pellets with a rate-limiting polymer containing the active drug. This formulation releases 70% of budesonide in the distal ileum and right sided colon [3], the main location of Crohn's disease lesions. In the present study, the release, absorption and plasma pharmacokinetics of budesonide were evaluated after administration of newly patented MMX®-tablets to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Budesonide has been formulated as an entericcoated controlled-release capsule used primarily in the treatment of inflammatory bowel disease. It has low systemic bioavailability while delivering active glucocorticoid to the distal small intestine and colon; as such, it is appropriate for Crohn's disease patients [11][12][13]. Recent studies have confirmed its efficacy in patients with celiac disease.…”
mentioning
confidence: 99%